A review of 3D bioprinting for organoids - Li Zeqing; Chen Long; Wu Jialin; Chen Yikang; Zhu Yizhun; Li Gang; Xie Guoxi; Tang Guosheng; Xie Maobin (Medical Review)
Current two-dimensional (2D) cell models for effective drug screening suffer from significant limitations imposed by the lack of realism in the physiological environment. Three-dimensional (3D) organoids models hold immense potential in mimicking the key functions of human organs by overcoming the limitations of traditional 2D cell models. However, current techniques for preparation of 3D organoids models had limitations in reproducibility, scalability, and the ability to closely replicate the complex microenvironment found in vivo. Additionally, traditional 3D cell culture systems often involve lengthy and labor-intensive processes that hinder high-throughput applications necessary for a large-scale drug screening. Advancements in 3D bioprinting technologies offer promising solutions to these challenges by enabling precise spatial control over cell placement and material composition, thereby facilitating the creation of more physiologically relevant organoids than current techniques. This review provides a comprehensive summary of recent advances in 3D bioprinting technologies for creating organoids models, which begins with an introduction to different types of 3D bioprinting techniques (especially focus on volumetric bioprinting (VBP) technique), followed by an overview of bioinks utilized for organoids bioprinting. Moreover, we also introduce the applications of 3D bioprinting organoids in disease models, drug efficiency evaluation and regenerative medicine. Finally, the challenges and possible strategies for the development and clinical translation of 3D bioprinting organoids are concluded.